Aquatic environmental characteristic of Singkil Swamp Wildlife Reserve in Aceh Singkil Regency - Nur Rohim; Sulistiono Sulistiono; Fredinan Yulianda (Depik, 2022)
Singkil Swamp Wildlife Reserve is a peat swamp ecosystem located in Aceh Singkil Regency, Aceh Province. Peat swamp ecosystem has an important function in protecting and balancing water systems, carbon stocks and biodiversity conservation. However, information on the characteristics of the waters of this ecosystem is still not widely known, especially in the area of utilization that is influenced by community activities. This study aims to determine the aquatic environmental characteristics of the Singkil Swamp Wildlife Reserve utilization area covering the physical and chemical parameters of the water and the relationship among those parameters. Sampling was carried out through field observations both in-situ and ex-situ at 5 stations for 3 months (April-June 2021). Observations were made on water quality parameters namely temperature, transparency, depth, current, colour, salinity, water smell, pH, DO, TDS, TSS, conductivity, phosphate and nitrate. Analysis of the data was conducted, namely correlation analysis, PCA (Principal Component Analysis) and CA (Cluster Analysis). The water color was black and the pH was acidic, that is a characteristic of the swamp waters. The results of the measurement of water quality parameters indicate that TDS (13-44 mg/l), TSS (9-236 mg/l), total phosphate (0.01-2.14 mg/l), and nitrate (0.5-25.7 mg/l) were suitable for freshwater aquaculture to support fishery reserve. Based on the clustering of those stations, 5 observation stations were grouped into two different groups, namely cluster 1 with the number of observation stations of 2 stations (Stations 1 and 2) and cluster 2 with the number of observation stations of 3 stations (3, 4 and 5). The parameter values of total phosphate, pH, DO, and nitrate in cluster 1 tend were higher than in cluster 2.Keywords:Peat swampFreshwaterWater quality